Rereading the Buenos Aires Action Plan - Ojeda Medina, Tahina (Revista Española de Desarrollo y Cooperación, 2023)
This article makes a revision of the Buenos Aires Action Plan (BAPA) of 1978. It does so from an International Relations approach, bringing it together with the dynamics of International Cooperation for Development. It presents an analysis of the political context and the events that left their mark on the formulation of the BAPA. It stuies the implications of this Plan of Action in the configuration of TCDC as a form of cooperation within the International System of Cooperation for Development and International Relations.
Keywords: BAPA; Technical cooperation; South-South Cooperation